(untitled) (American Journal of Islam and Society, 2001)
The poet-philosopher Muhammad Iqbal (1877-1938) of the Indian subcontinent, who has been called the most serious Muslim philosophical thinker of modem times by Fazlur Rahman, does not occupy the place he deserves in the memory of the ’Umma of Islam today. For this fallen ’Umma which has not produced world-class thinkers for centuries, this state of amnesia cannot be afforded if the desire for revival is genuine. To this end, I believe, the recent book of Mustansir Mir, Tulip in the Desert: A Selection of the Poetry of Muhammad Iqbal is a very timely contribution. The book consists of twelve short chapters preceded by an introduction on the life, poetry and philosophy of Iqbal. The author, who edited and translated this selection from Urdu and Farsi, is a professor in the Department of Philosophy and Religious Studies at Y oungston State University, Ohio. His book is more than a collection of Iqbal’s poetry. He puts his own background to the service of the reader. Each chapter starts with a commentary on the poems selected according to a theme. Each poem is supplied with extensive explanatory notes, which sometimes take more space than the poem itself. As the author rightly states, these commentaries and notes elucidate Iqbal’s use of historical, religious, philosophical and literary resources of the Islamic tradition. The book is a comprehensive introduction to various aspects of Iqbal’s ideology and art in his poetry. Considering that the number of existing books on Iqbal is far less than sufficient as compared to the magnitude and importance of his work, the present one is a significant contribution to commemorate Iqbal, and teach lay people, as well as the learned, his recipe for overcoming the problems that Muslims have been facing for centuries ...